Soft-tissue esthetic outcome of single implants: Immediate placement in fresh extraction sockets versus conventional placement in healed sockets - Nima Naddaf Pour; Baharak Ghaedi; Mona Sohrabi (Journal of Indian Society of Periodontology, 2018)
Background: Immediate implant placement has advantages such as requiring fewer surgical procedures and decreased treatment time; however, unpredictable soft- and hard-tissue outcome is a problem. This study aimed to compare the soft-tissue esthetic outcome of single implants placed in fresh extraction sockets versus those placed in healed sockets. Materials and Methods: This cross-sectional, retrospective study was performed on 42 patients who received single implants. Twenty-two patients with a mean age of 40.14 years received immediate implants while 18 patients with a mean age of 43.40 years were subjected to conventional (delayed) implant placement. The mean follow-up time was 14.42 ± 8.37 months and 18.25 ± 7.10 months in the immediate and conventional groups, respectively. Outcome assessments included clinical and radiographic examinations. The esthetic outcome was objectively rated using the pink esthetic score (PES). Results: All implants fulfilled the success criteria. The mean PES was 8.54 ± 1.26 and 8.10 ± 1.65 in the immediate and conventional groups, respectively. This difference was not statistically significant (P = 0.329). The two PES parameters, namely, the facial mucosa curvature and facial mucosa level had the highest percentage of complete score. Conclusions: Immediate and conventional single implant treatments yielded comparable esthetic outcomes.